Ks. Władysław Wanags MIC i jego posługa na Podolu w latach 1977-2001 - Biletska, Mariia (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The article presents Rev. Władysław Wanags, a Marian priest, and his achievements. He was born in Latvia, but most of his life spent in Soviet Ukraine working among the Catholics in Podolia. As an adult, he experienced inner conversion, which resulted in the choice of the priestly life. After a brief ministry in Latvia, he was directed by the church authorities to work in Ukraine in 1971. He became famous for uncompromising nature and courage that won him the respect from the faithful and the local party apparatus. He worked strenuously and served the congregation at a time when the communist authorities fought with religion and obstructed pastoral work. Rev. Wanags became famous as a great builder. He initiated and often actively participated in building twenty new churches, twenty-nine parish houses, two buildings for the seminary, a house for the poor and the elderly. All these buildings were erected within 10 years. He also managed to restore nine historic churches which had been ruined for decades. Even now the churches erected by him are called "wanagsowe" because of their appearance.